Large maternal waist circumference in relation to height is associated with high glucose concentrations in an early‐pregnancy oral glucose tolerance test: A population‐based study - Mervi Jokelainen; Beata Stach‐Lempinen; Kari Teramo; Arja Nenonen; Hannu Kautiainen; Miira M. Klemetti (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction To explore the role of maternal anthropometric characteristics in early‐pregnancy glycemia, we analyzed the associations and interactions of maternal early‐pregnancy waist circumference (WC), height and pre‐pregnancy body mass index (BMI) with plasma glucose concentrations in an oral glucose tolerance test (OGTT) at 12–16 weeks’ gestation. Material and Methods A population‐based cohort of 1361 pregnant women was recruited in South Karelia, Finland, from March 2013 to December 2016. All participants had their WC, weight, height, HbA1c, and blood pressure measured at 8–14 weeks’ gestation and subsequently underwent a 2‐h 75‐g OGTT, including assessment of fasting insulin concentrations, at 12–16 weeks’ gestation. BMI (kg/m2) was calculated using self‐reported pre‐pregnancy weight. Maternal WC ≥80 cm was defined as large. Maternal height ≥166 cm was defined as tall. Data on gestational diabetes treatment was extracted from hospital records. Results In the total cohort, 901 (66%) of women had an early‐pregnancy WC ≥80 cm, which was associated with higher early‐pregnancy HbA1c, higher concentrations of  fasting plasma glucose and serum insulin, higher post‐load plasma glucose concentrations, higher HOMA‐IR indices, higher blood pressure levels, and higher frequencies of pharmacologically treated gestational diabetes, than early‐pregnancy WC <80 cm. Maternal height ≥166 cm was negatively associated with 1‐ and 2‐h post‐load plasma glucose concentrations. Waist‐to‐height ratio (WHtR) >0.5 was positively associated with both fasting and post‐load plasma glucose concentrations at 12–16 weeks’ gestation, even when adjusted for age, smoking, nulliparity, and family history of type 2 diabetes. The best cut‐offs for WHtR (0.58 for 1‐h plasma glucose, and 0.54 for 2‐h plasma glucose) were better predictors of post‐load glucose concentrations >90th percentile than the best cut‐offs for BMI (28.1 kg/m2 for 1‐h plasma glucose, and 26.6 kg/m2 for 2‐h plasma glucose), with areas‐under‐the‐curve (95% confidence interval) 0.73 (0.68–0.79) and 0.73 (0.69–0.77), respectively, for WHtR, and 0.68 (0.63–0.74) and 0.69 (0.65–0.74), respectively, for BMI. Conclusions In our population‐based cohort, early‐pregnancy WHtR >0.5 was positively associated with both fasting and post‐load glucose concentrations at 12–16 weeks’ gestation and performed better than BMI in the prediction of post‐load glucose concentrations >90th percentile. Overall, our results underline the importance of evaluating maternal abdominal adiposity in gestational diabetes risk assessment.